The Qur’ān and Kerygma: Biblical Receptions of the Muslim Scripture across a Millennium by Jeffrey Einboden (American Journal of Islam and Society, 2020)
The relationship between the Bible and the Qur’an is usually considered in a one-dimensional manner. Virtually all studies have tended to read the Islamic text in light of the biblical one, with particular interest in the possible ways the Bible might have left its mark on the Qur’an. The presence of shared characters and traditions in both scriptures perhaps makes such an approach inevitable, and the Bible’s chronological primacy as the earlier of the two works has encouraged a one-way understanding of their connection. According to this thinking, because the Bible predates the Qur’an and the two share certain features, any influence between them could have gone in only a single direction—from the earlier biblical text to the later qur’anic one. Previous scholarship in this area tended to posit the Qur’an’s direct dependence on the Bible. Although that mindset has persisted in some quarters, more recent work often offers a more nuanced perspective that highlights the Islamic text’s creative reimagining and interpretation of the individuals and stories found in the Qur’an and the Bible.Download